Premarital Sex in Biblical Law: a Cross-Cultural Perspective - Shveka, Avi (Vetus Testamentum, 2020)
It is commonly held in recent scholarship that biblical law, like the society in which it was generated, did not regard premarital sex as a severe offence. The law of the slandered bride (Deut 22:13-22), which determines that a bride that was found non-virgin on her wedding night shall be killed, has therefore become during the last decades a riddle for biblical law researchers, who try to explain the girl's sin in various ways. We claim that this view ignores the wealth of ethnographic data that shows that harsh treatment of premarital sex is common, especially in patrilineal and patrilocal societies (as was ancient Israelite society). Moreover, a reexamination of other biblical laws regarding sexual conduct in light of the same ethnographic data shows that they reflect the very same attitudes. The different laws are not contradictory but rather complementary—all reflecting a typical patriarchal, androcentric, traditional society.